Monitoring and Prudence - Luca Beltrametti; Gabriele Cardullo (Institute of Labor Economics (IZA), 2024)
We study the impact of monitoring in a workplace context where both firms and employees are unable to perfectly observe the individual worker contribution to total output. Therefore, in our setting monitoring is not aimed at reducing information asymmetries but still affects effort and output. We show that if individuals are prudent, firms call for less monitoring. Workers' stance towards monitoring is ambiguous and depends on risk aversion and the disutility of effort. Our "prudence effect" offers some clues for a more nuanced interpretation of the attitudes towards monitoring by firms and workers.
Keywords: D81; J24; M52; 330; monitoring; prudence; workers' effort